Sikap dan Perilaku Perawat Berpengaruh terhadap Pelaksanaan Timbang Terima di Ruang Rawat Inap RSJ Sambang Lihum - Noor Amaliah; Akhmad Syarif; Iswantoro Iswantoro (Malahayati Nursing Journal, 2023)
ABSTRACT Handover is a technique or way to convey and receive something (report) related to the patient's condition. Inaccurate information in handover can have a serious impact on patients, almost 70% of incidents that cause disability or death are due to poor communication. Many factors influence the implementation of the handover, one of which is the attitude and behavior of a nurse. The purpose of the study was to determine the relationship between the attitudes and behavior of nurses with the implementation of the handover in the Inpatient Room of Sambang Lihum Hospital. The research design used was cross-sectional. The study was conducted at Sambang Lihum Hospital with a sample of 135 nurses using a purposive sampling technique. The study was conducted in December 2019. The research used questionnaires and observation sheets. Data analysis using univariate and bivariate with Spearman rank test. The results of the research on the attitude factor of the implementing nurses were in a good category (83.70%), with the behavior of the implementing nurses in the positive category (66.67%), most of the nurses were in a good category (66.67%) in the implementation of the handover. There is a relationship between the attitude and behavior of nurses with the implementation of handover in the Inpatient Room of the Sambang Lihum Hospital.  Keywords: Attitude, Behavior, Implementation Of Handover  ABSTRAK Timbang terima merupakan teknik atau cara untuk menyampaikan dan menerima sesuatu (laporan) yang berkaitan dengan keadaan pasien. Ketidakakuratan informasi dalam melakukan timbang terima dapat menimbulkan dampak yang serius pada pasien, hampir 70% kejadian yang menyebabkan kecacatan atau kematian disebabkan karena buruknya komunikasi. Banyak faktor yang mempengaruhi pelaksanaan timbang terima salah satunya yaitu sikap dan perilaku seorang perawat. Tujuan penelitian adalah untuk mengetahui hubungan sikap dan perilaku perawat dengan pelaksanaan timbang terima di Ruang Rawat Inap RSJ Sambang Lihum. Desain penelitian yang digunakan adalah cross sectional. Penelitian dilakukan di RSJ Sambang Lihum dengan Sampel 135 perawat menggunakan teknik purposive sampling. Penelitian dilakukan bulan Desember 2019. Peneltian menggunakan kuesioner dan lembar observasi. Analisa data menggunakan univariat dan bivariat dengan uji spearman rank. Hasil penelitian faktor sikap perawat pelaksana kategori baik (83,70%), dengan perilaku perawat pelaksana kategori positif (66,67%), sebagian besar dari perawat pelaksana kategori baik (66,67%) dalam pelaksanaan timbang terima. Ada hubungan sikap dan perilaku perawat dengan pelaksanaan timbang terima di Ruang Rawat Inap RSJ Sambang Lihum. Kata Kunci: Sikap, Perilaku, Pelaksanaan Timbang Terima